2009
DOI: 10.1063/1.3110963
|View full text |Cite
|
Sign up to set email alerts
|

Electric field control of room temperature ferromagnetism in III-N dilute magnetic semiconductor films

Abstract: We report on the electrical field control of ferromagnetism ͑FM͒ at room temperature in III-N dilute magnetic semiconductor ͑DMS͒ films. A GaMnN layer was grown on top of an n-GaN substrate and found to be almost always paramagnetic. However, when grown on a p-type GaN layer, a strong saturation magnetization ͑M s ͒ was observed. This FM in GaMnN can be controlled by depletion of the holes in the GaMnN/p-GaN/n-GaN multilayer structures. We have demonstrated the dependence of the FM on the thickness of the p-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Indeed, a number of experiments have shown that an increased hole concentration in Ga 1−x Mn x N from codoping with p-type elements such as Mg improves the ferromagnetic properties. 28,[53][54][55] The difficulty in achieving an efficient p-type doping of GaN ensures that this method of encouraging ferromagnetism in Ga 1−x Mn x N remains a significant challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of experiments have shown that an increased hole concentration in Ga 1−x Mn x N from codoping with p-type elements such as Mg improves the ferromagnetic properties. 28,[53][54][55] The difficulty in achieving an efficient p-type doping of GaN ensures that this method of encouraging ferromagnetism in Ga 1−x Mn x N remains a significant challenge.…”
Section: Discussionmentioning
confidence: 99%
“…With the manipulation of carrier spins, a new generation of nonvolatile (green) computing systems could be eventually developed for many low-power-dissipation applications in all fields, including sensor network, health monitoring, information, and sustainable wireless system. Since Datta and Das [131] first introduced the concept of spin FETs in 1990, enormous efforts were dedicated to creating a device wherein the carrier transport is modulated by electrostatic control of carrier spins [2,20,22,23,[132][133][134][135][136]. To understand and exploit this controllability, several theoretical models were proposed to explain the ferromagnetic coupling in DMS on a microscopic scale (also elaborated in the theoretical section): the Zener Kinetic-exchange [10], double-exchange [137], and the RKKY interaction [138,139].…”
Section: Electric-field-controlled Ferromagnetismmentioning
confidence: 99%
“…In these materials, high magnetic impurity concentrations are needed due to the lack of longrange interaction among magnetic spins. However, there have been only limited reports on the carrier mediated effect in the wide band gap materials at room temperature [20][21][22]. Though considerable amount of work has been done on III-V and II-VI DMSs [2,23], the lack of high T c and the difficulty in achieving electric field modulated ferromagnetism (carrier-mediated ferromagnetism) at or above room temperature deters them from being considered for semiconductor integration.…”
Section: Introductionmentioning
confidence: 99%
“…In these materials, high magnetic impurity concentrations are needed due to the lack of long-range interaction among magnetic spins. However, there have been only limited reports on the carrier mediated effect in the wide band gap materials at room temperature (Nepal et al, 2009, Kanki et al, 2006, Philip et al, 2006. Though considerable amount of work has been done on III-V and II-VI DMSs , Chiba et al, 2006a, the lack of high T c and the difficulty in achieving electric field modulated ferromagnetism (carrier mediated ferromagnetism) at or above room temperature deters them from being considered for semiconductor integration.…”
Section: Introductionmentioning
confidence: 99%
“…With the manipulation of carrier spins, a new generation of nonvolatile (green) computing systems could be eventually developed for many low-powerdissipation applications in all fields, including sensor network, health monitoring, information, sustainable wireless system, etc. Since Datta and Das (Datta and Das, 1990) first introduced the concept of spin FETs in 1990, enormous efforts were dedicated to creating a device wherein the carrier transport is modulated by electrostatic control of carrier spins (Philip et al, 2006, Appelbaum and Monsma, 2007, Chiba et al, 2006a, Nazmul et al, 2004, Nepal et al, 2009, Koo et al, 2009, Chiba et al, 2008, Boukari et al, 2002. To understand and exploit this controllability, several theoretical models were proposed to explain the ferromagnetic coupling in DMS on a microscopic scale (also elaborated in the theoretical section): the Zener Kinetic-exchange (Jungwirth et al, 2006), double-exchange , the RKKY interaction (Matsukura et al, 1998, Yagi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%